Systematic Evaluation of Deep Learning Paradigms for Speech Emotion Recognization Using Diverse Audio Sources (International Journal of Scientific Research in Science and Technology, 2025)
Speech emotion identification is one of the most difficult areas of human-computer interaction, with significant ramifications for assistive technologies, customer support, and mental health monitoring. Despite significant advances in machine learning, accurately identifying emotional states from speech remains difficult due to the complex, nuanced nature of vocal emotional expressions across diverse speakers and contexts. This study presents a comprehensive evaluation of Speech Emotion Recognition (SER) systems across multiple machine learning paradigms using four benchmark datasets (CREMA-D, RAVDESS, SAVEE, and TESS). We implement a multi-feature extraction approach incorporating prosodic, spectral, and voice quality features, while employing data augmentation techniques to enhance model robustness. Our investigation spans traditional machine learning algorithms, ensemble methods, and deep learning architectures including CNN and RNN implementations. Performance evaluation reveals the superiority of the Stacking Classifier (accuracy: 72.54%, F1-score: 72.47%), with strong performances from Random Forest (68.31% accuracy) and ResNet (66% accuracy). This comparative analysis advances affective computing by providing detailed insights into the effectiveness of various approaches for emotion recognition in speech, with significant implications for developing more sophisticated emotional intelligence systems.